2016
DOI: 10.1113/ep085852
|View full text |Cite
|
Sign up to set email alerts
|

Gradual downhill running improves age‐related skeletal muscle and bone weakness: implication of autophagy and bone morphogenetic proteins

Abstract: Edited by: Philip Atherton New Findings r What is the central question of this study?Exercise training by running has an effect on age-related muscle and bone wasting that improves physical activity and quality of life in the elderly. However, the effect of downhill running on age-related muscle and bone wasting, and its mechanisms, are unclear. r What is the main finding and its importance?Gradual downhill running can improve skeletal muscle growth and bone formation by enhancing autophagy and bone morphogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…For a mountain marathon, the decrease in elasticity could have smaller consequences, due to the fact that in downhill running elasticity of tendons are less important than when running in the flat with the importance of storage of (elastic) energy [40]. The mentioned premise is supported that in collagen tissue alterations of matric proteins and proteoglykans with reduced plasticity and elasticity of ligaments and tendons with increased stiffness result [40][41][42]. Training of these structures could lead to an improvement of age-associated decrease and improve general performance of seniors [36,43].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…For a mountain marathon, the decrease in elasticity could have smaller consequences, due to the fact that in downhill running elasticity of tendons are less important than when running in the flat with the importance of storage of (elastic) energy [40]. The mentioned premise is supported that in collagen tissue alterations of matric proteins and proteoglykans with reduced plasticity and elasticity of ligaments and tendons with increased stiffness result [40][41][42]. Training of these structures could lead to an improvement of age-associated decrease and improve general performance of seniors [36,43].…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, associated structures of collagen tissue (tendons and ligaments) are to mention which lose elasticity with increasing age [19,[40][41][42]. For a mountain marathon, the decrease in elasticity could have smaller consequences, due to the fact that in downhill running elasticity of tendons are less important than when running in the flat with the importance of storage of (elastic) energy [40].…”
Section: Discussionmentioning
confidence: 99%
“…It also promoted growth, repair, and remodeling of muscle by the increment of muscle growth factors including p‐AKT, p‐mTOR, MyoD, and myogenin in skeletal muscles of OVX rats. H&E and IHC (p‐mTOR and MyoD) results further confirmed these findings and suggested that C1 treatment protected the structural integrity following gross injuries including polymyositis and strain in OVX rats soleus muscle (Kim et al, ).…”
Section: Discussionmentioning
confidence: 68%
“…Therefore ageing results in slower recovery and functional and structural deficits (McArdle, Vasilaki, & Jackson, ). There are many factors that contribute to osteoporosis and sarcopenia, such as nutritional deficiencies, heredity, oestrogen deficiency, chronic diseases and ageing (Guillemant, Accarie, Peres, & Guillemant, ; Kim, Jeong, Han, & Yi, ; Kim, Lee, & Yi, ). Therefore, prophylactic interventions are needed for the suppression of age‐related skeletal muscle wasting and bone loss after menopause.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of exercise training is related to the mechanical stimulation on bone caused by contraction of muscle (Oh, Tanaka, Naka, & Igawa, ). Until now, various modes of exercise, such as treadmill running, resistance and swimming training, have been used in many animals to investigate the effect of exercise training (Kim et al., ; Oh et al . ; Sanches, Conti, Sartori, Irigoyen, & De Angelis, ).…”
Section: Introductionmentioning
confidence: 99%